Imobilização de Complexos de Rutênio com Ligantes Fosfínicos e Polipiridínicos em Matriz de Sílica com Potencial Aplicação Catalítica - Bernardo, Ricardo Douglas de Sousa (2023)
Porous silicate materials have been used as solid support for several compounds for a myriad of applications due to large surface areas, thermal stability, and easiness of functionalization. Among the applications, heterogeneous catalysis can be mentioned, which arouses interest in basic and technological science. In this context, the goal of this work was to produce silicate-based porous materials modified with ruthenium complexes able to act as heterogenous catalysts in hydrogenation reactions. For the incorporation of the complexes onto the solid silica support, a covalent route was adopted starting with the functionalization of this material with 3-aminopropyltrietoxisilane (APTS) followed by the reaction with isonicotinic acid (ISN) resulting in the formation of mPSi-APTS-ISN. This material, in turn, was reacted with the cis-[Ru(Cl)2(phen)(dppb)], mer-[Ru(Cl)3(OH2)(dppb)], [Ru(Cl)2(PPh3)(binap)], and [Ru(PPh3)2(salen)] complexes producing four new materials, namely mPSi-APTS-ISN-RuCl(phen); mPSi-APTS-ISN-Ru(OH2)(Cl)2; mPSi-APTS-ISN-Ru(binap) e mPSi-APTS-ISN-Ru(salen). The obtained materials were characterized by vibrational and electronic spectroscopies, nuclear magnetic resonance (13C, 29Si and 31P{1H}), scanning electron microscopy, electrochemical techniques, elemental analysis, thermogravimetry, and N2 adsorption/desorption isotherms, among others. The adsorption/desorption isotherms indicated the production of a porous material composed, mainly, by micropores and with a significant amount of mesopores. After the characterization, the materials were applied in catalytic assays using, as a standard process, the hydrogenation reaction of acetophenone. The assays were monitored by gas chromatography coupled to mass spectrometry in several conditions of time and temperature, keeping constant the H2 pressure at 2 atm. All the materials but mPSi-APTS-ISN-Ru(OH2)(Cl)2 showed promising conversions, assuming the active species (complexes) are supported on solid matrices. The highest conversion (50 %) was observed for the mPSi-APTS-ISN-RuCl(phen) material at 110 oC and 8 h of reaction. At a milder condition (60 oC) and just 2 h of reaction, the mPSi-APTS-ISN-Ru(salen) material showed a conversion of 35 %. These results are indeed quite promising if considering these materials combine reasonable conversion values with relatively mild conditions and the easiness of recovering being in line with the awareness of environmental sustainability.